A qualitative descriptive study of Thai fathers’ experiences in supporting their partners’ breastfeeding - Patcharin Ngoenthong; Nantaporn Sansiriphun; Warunee Fongkaew; Nonglak Chaloumsuk (Belitung Nursing Journal, 2023)
Background: The crucial role of fathers in the well-being of mothers and infants is widely acknowledged. This study focuses on the specific context of how Thai fathers support their partners in breastfeeding, with the goal of gaining a deeper understanding of the strategies they employ in providing this support. Objective: This study aimed to explore the experiences of fathers in supporting their partners in breastfeeding. Methods: The study used a qualitative descriptive design from December 2018 to February 2020. Nineteen Thai fathers were purposefully selected, each with partners and infants who did not face any complications that would serve as barriers to breastfeeding. Data collection occurred at vaccination clinics and family planning wards in two major hospitals in Chiang Mai province, Thailand. The data were collected through in-depth interviews, and a thematic analysis approach was employed for data analysis. Results: Four themes emerged: a) Facing barriers to breastfeeding support, b) Believing in the value of breast milk, c) Seeking ways to increase milk supply, and d) Making an effort to support continued breastfeeding. Conclusion: Thai fathers demonstrated a strong eagerness to support their partners in sustaining breastfeeding. Their willingness highlights the importance of nurses, midwives, and other healthcare providers providing additional education and support to empower them as supportive partners to mothers.